Praticas educativas: limites entre o bater e o não bater : contribuições ao estudo da violência Intrafamiliar - Martins, Mary Anne Fontenele (2002)
The purpose of this study is to comprehend the meaning of bodily physical and/or psychological punishment as a disciplinary method adopted by parents, identifying factors that influence them in their ch.ildren’s discipline and the parents’ knowledge on their experiences, feelings, definitions, altitudes and opinions around the educational disciplinary process. We assume that the root of social violence comes from already established family relationships and are built in everyday routines of the family system. Under the guise of discipline, added to their own cultural baggage, parents, with their parental authoríty, or others who are in charge mistreat and beat their children as if they were objects - things to unload their own frustrations, fears and anguish ~ who live in modern society, thus creating a vicious circle. A selective study was made with parents in 4 Varas do Pirambu community, in Ceará and SOS-Children in 2001. The data was gathered through 12 semi-structured in-depth interviews and focus groups. We used practical discussions as the central focal point for constructive approach and it was possible to reproduce the families’ daily routines with parents-children relationships through the development of 27 “meaning” diagrams, We developed a theoretical model relating disciplinary practices about the concept on the limit of spanking or not spanking in parents-children relations. We took in consideration the social realm they live in and how this social realm .reflects in those disciplinary practices. We tried to identify with the parents’ discussions the meanings given to those disciplinary practices and we established 7 factors: Trans-generation identification model; mternalized exíra- familiar social violence model; parenthood self-perception; childreifs concepís; power relations; reasons to spank; social control. This study points out to us how to understand that the act of spanking children is appropriate to impose order and to maintain a domínant-submissive relationship, We observed that in the society’s eyes, there is a clear difference between spanking for the purpose of mistreating someone and spanking to impose discipline, although everyone practices the latter. The limit, they say, is the physical strength at the time of spanking: a swat doesn’t hurt, beating does. In this context, there isn't violence in the perception of parents who spank. They dorft understand the limit between violence and non-violence, but are instead, doing the correct disciplinary process. We checked that childrerfs concept, the internalized intra and extra familiar models, established power relations and the everyday violence are drfferent between those parents who spank and those who don’t. We would like to híghlight that the trans-generation aspect exerts influence in the disciplinary style adopted by the parents and adds incisively in this discussion. In this way, we received assorted and complex answers from parents who show a need for the development of a project that tries to educate parents, informing and preparing them for their special roles in disctplining their children even in the most primitive and adverse social settings and the current inhumane and unequal economic system. We recommend interaction in all sectors of society, government and non-government agencies, so there can exist a culture of tolerance, dialogue and mutual respect between parents and children and a new social practice of understanding. Perhaps we can leam and follow the examples from our Indian natives who knew how to discipline withoiH spanking.